Proses Pencucian dan Angka Lempeng Total (ALT) Piring Penjual Lotek di Kelurahan Surau Gadang Kecamatan Nanggalo Kota Padang - Burhan Muslim; Haryuki Dwi Putri; Suksmerri (CV. CENDIKIA JENIUS INDONESIA, 2024)
Cutlery is one of the factors that play a role in disease transmission, because cutlery that is not clean and contains microorganisms can transmit disease through food. The purpose of this study was to determine the description of the washing process and the Total Plate Count on lotek seller plates in Surau Gadang Village, Nanggalo District in 2022. This type of research is descriptive. When the study was conducted in January - May 2023. The population of this study was 10 lotek sellers who were observed in washing facilities and washing techniques, while for the Total Plate Count Test samples were taken by purposive sampling method on 4 lotek sellers. Data obtained from the inspection results are processed manually and presented in tabular form. Dish washing facilities for 10 lotek sellers are 5 bad lotek sellers. Dish washing technique with 4 lotek sellers is not good. Total Plate Count in 4 lotek seller samples did not meet the requirements based on the Regulation of the Minister of Health of the Republic of Indonesia Number 1096 / Menkes / Per / VI / 2011 About Jasaboga Sanitary Hygiene. Based on the results of the research, it is known that the washing process influences the results of the Total Plate Count so that none of the lotek seller plates in Surau Gadang Village are eligible. Therefore, it is recommended that lotek sellers wash dishes using running water.